Verification of a rapid mooring and foundation design tool. (February 2018) - Weller, Sam D; Hardwick, Jon; Gomez, Steven; Heath, Jason; Jensen, Richard; Mclean, Niall; Johanning, Lars
Marine renewable energy devices require mooring and foundation systems that suitable in terms of device operation and are also robust and cost effective. In the initial stages of mooring and foundation development a large number of possible configuration permutations exist. Filtering of unsuitable designs is possible using information specific to the deployment site (i.e. bathymetry, environmental conditions) and device (i.e. mooring and/or foundation system role and cable connection requirements). The identification of a final solution requires detailed analysis, which includes load cases based on extreme environmental statistics following certification guidance processes. Static and/or quasi-static modelling of the mooring and/or foundation system serves as an intermediate design filtering stage enabling dynamic time-domain analysis to be focused on a small number of potential configurations. Mooring and foundation design is therefore reliant on logical decision making throughout this stage-gate process. The open-source DTOcean (Optimal Design Tools for Ocean Energy Arrays) Tool includes a mooring and foundation module, which automates the configuration selection process for fixed and floating wave and tidal energy devices. As far as the authors are aware, this is one of the first tools to be developed for the purpose of identifying potential solutions during the initial stages of marine renewable energy design. While the mooring and foundation module does not replace a full design assessment, it provides in addition to suitable configuration solutions, assessments in terms of reliability, economics and environmental impact. This article provides insight into the solution identification approach used by the module and features the verification of both the mooring system calculations and the foundation design using commercial software. Several case studies are investigated: a floating wave energy converter and several anchoring systems. It is demonstrated that the mooring and foundation module is able to provide device and/or site developers with rapid mooring and foundation design solutions to appropriate design criteria.